An assessment on the behavioral foundations of electoral decisions in the 2015 Turkish general elections. (2nd January 2016) - Erisen, Cengiz
ABSTRACT: Turkish politics has overcome several challenges in order to reach a situation with less political uncertainty. Among several issues, voter behavior in the two recent general elections in 2015 is a major topic of interest. In this think-piece, I discuss the behavioral indicators of vote choice and political judgments between the two 2015 elections. To that end, I first explore the context of public polarization before introducing the behavioral approaches to explain voter behavior. I use nationally representative survey data in order to make descriptive inferences that shed light on the unexpected change in electoral behavior.